Pandangan M. Syarur terhadap Pendekatan Bahasa: Tafsir Lugawi - Fadillah, Insan; Balqis, Sabila Phutri; Zein, Achyar; Astuti, Rahayu Fuji (IAI Nasional Laa Roiba Bogor, 2024)
In the process of interpreting the Al-Qur’an, interpretive scholars mobilize their spiritual energy so that all levels of society can understand the Al-Qur’an. A very important approach in understanding the Al-Qur’an is the linguistic approach or what is known as Lugawi interpretation. Lugawi interpretation is needed to understand the Al-Qur'an. Apart from using the Arabic Al-Qur’an which is full of literature, balaghah, fashahaha, gender, parables and rhetoric, the Al-Qur'an also appeared in the heyday of poetry and linguistics. During the first days of Islam, some people embraced Islam simply because of their love of the language and eloquence of the Koran. In this journal, we will examine the interpretation of the Koran using Lugawi's strategy.